If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 1) = (2x + -3) Reorder the terms: (1 + 5x) = (2x + -3) Remove parenthesis around (1 + 5x) 1 + 5x = (2x + -3) Reorder the terms: 1 + 5x = (-3 + 2x) Remove parenthesis around (-3 + 2x) 1 + 5x = -3 + 2x Solving 1 + 5x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 5x + -2x = -3 + 2x + -2x Combine like terms: 5x + -2x = 3x 1 + 3x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 3x = -3 + 0 1 + 3x = -3 Add '-1' to each side of the equation. 1 + -1 + 3x = -3 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = -3 + -1 3x = -3 + -1 Combine like terms: -3 + -1 = -4 3x = -4 Divide each side by '3'. x = -1.333333333 Simplifying x = -1.333333333
| 9+3(2x+4)=33 | | 6-7x=5x-8x-2 | | px-4=q | | x/0.9=8.9 | | .01(x+5)-.5=.1(6x+5) | | y=-4.9x+10.9 | | 4x+190=300 | | 3(x+6)=5x+22 | | x^2-1x+2=0 | | 6(1+x)=-6+8x | | 100x=150 | | x^2+2x-6=20 | | 14-x=2x-1 | | .01(x+7)-.7=.1(8x+7) | | 150y=150 | | 3(q-5)=2(q/5) | | -8(3n+7)=-31+n | | 38=26s-7s | | -2+5x+8=6(x+2)-6 | | n^2-2n-70=0 | | x^2=-x^2-2x-6 | | .01(x+7)-.25=.1(8x+7) | | 7y+4=2(y-8) | | -62x=806 | | 4y/n=3f | | -14=3.6 | | 17=-5+32 | | solvex^2+7x-60=0 | | 8-2x=3x+28 | | 14r-6r=48 | | -54+9= | | 44m=-4092 |